De novo loss‐of‐function variant in PTDSS1 is associated with developmental delay. Issue 6 (27th February 2022) - Gracie, Sara; Sengupta, Nivedita; Ferreira, Carlos; Pemberton, Joshua; Anderson, Ilse; Wang, Xin; Rhodes, Lindsay; Brown, Kathleen; Balla, Tamas; Larson, Austin
Abstract: Heterozygous de novo missense pathogenic variants in PTDSS1 that result in gain‐of‐function of phosphatidylserine synthase 1 are associated with Lenz–Majewski hyperostotic dwarfism (LMHD). We identified the novel heterozygous de novo variant p.(Leu137Phe) in PTDSS1 in a child with mild‐to‐moderate developmental delay. Skeletal survey revealed no evidence of LMHD in this patient. Functional assessment of the p.Leu137Phe variant was performed by overexpressing the mutant protein into HEK293 cells. Following C 14 ‐serine labeling and TLC analysis of lipids, we observed that the p.(Leu137Phe) variant displayed no catalytic activity compared to the wild‐type enzyme. We conclude that p.(Leu137Phe) variant has decreased enzymatic activity and that is likely to be the etiology of the patient's symptoms given the gene's constraint in the population. This is the first report of the clinical phenotype seen in an individual with a heterozygous loss‐of‐function variant in PTDSS1 . This phenotype is distinct from LMHD, which results from gain‐of‐function pathogenic variants in the same gene. Evaluation of the neurodevelopmental phenotype of additional individuals with loss‐of‐function variants in PTDSS1 is indicated to determine the spectrum of associated phenotypes.